PHYSICOCHEMICAL INVESTIGATIONS OF VERMICULITE – MICROPOROUS COMPONENT FOR HEAT-RESISTANT MATERIALS - Bazhirov Tynlybek Saifutdinovich,; Protsenko Vyacheslav Sergeyevich,; Bazhirov Nurlybek Saifutdinovich,; Dauletiyarov Mukhtar Srazhevich,; Serikbayev Bolatzhan Yermahanovich,; Bazhirova Kamshat Nurlybekovna, (Academic Scientific Journal of Chemistry, 2019)
The results of investigations of Kulantau field (Turkestan region) vermiculite’s physicochemical and physical-technical properties are presented. The vermiculite’s chemical and mineralogical composition and its main crystalline phases, which are composed of ferrous magnesium and calcium aluminosilicates of complex composition, are determined by chemical, X-ray diffraction, spectral analysis methods. The complex thermal analysis method established the processes occurring during heating, which allow to judge the physicochemical and structural changes occurring in vermiculite during heat treatment. The electron microscopy method investigated the vermiculite particles’ surface morphology. The main physical-technical properties of the expanded vermiculite are determined. It was established that the expanded vermiculite has low bulk density and low thermal conductivity, has high porosity, fire resistance, and refractoriness characteristics. Due to its unique properties, the expanded vermiculite can be effectively used as a microporous component for production of composite heat-resistant materials.